Development of a Digital PPE Request and Approval System for Industrial Safety Using Microsoft Power Platform - Nur Dini Hairul,; Mohd Akhir Ahmad,; Amru Daud, (Progress in Engineering Application and Technology, 2026)
Personal Protective Equipment (PPE) plays a critical role in safeguarding workers from potential hazards in industrial settings. However, traditional methods of PPE request and approval are often cumbersome, paper-based, and inefficient. This study presents the development of a digital PPE request and approval system for industrial safety, implemented using the Microsoft Power Platform, including Power Apps, Power Automate, and Microsoft Lists. The objective of the system was to replace manual processes with a streamlined digital approach to improve efficiency, traceability, and communication. The system allows employees to submit PPE requests, track their status, and obtain approval without delays. It also provides real-time updates and centralizes data for better record-keeping. Results from a two-week pilot trial at Synthomer Sdn. Bhd. indicated that the digital system significantly reduced approval times, minimized delays in PPE issuance, and enhanced operational transparency. Feedback from users highlighted the system's ease of use, faster response times, and overall positive impact on PPE management, proving that digital transformation can improve safety compliance and operational efficiency.